Hospital‐Acquired Hyperkalemia Events in Older Patients Are Mostly Due to Avoidable, Multifactorial, Adverse Drug Reactions. Issue 3 (3rd November 2018) - Robert, Laurine; Ficheur, Grégoire; Décaudin, Bertrand; Gellens, Juliette; Luyckx, Michel; Perichon, Renaud; Gautier, Sophie; Puisieux, François; Chazard, Emmanuel; Beuscart, Jean‐Baptiste
Abstract : Drug‐induced hyperkalemia is a frequent and severe complication in the hospital setting. Other risk factors may also induce hyperkalemia but the combination of drugs and precipitating factors has not been extensively studied. The aim was to identify drug‐induced hyperkalemia events in hospitalized older patients and to describe their combinations with precipitating factors. Two experts independently analyzed retrospective data of patients aged 75 years or more. Experts identified 471 hyperkalemia events and concluded that 379 (80.5%) were induced by drugs. The cause was multifactorial (i.e., at least one drug with a precipitating factor) in 300 (79.2%) of the 379 drug‐induced hyperkalemia. Most of the drug‐induced hyperkalemia events were avoidable (79.9%)—mainly because of the multifactorial cause (e.g., dosage adaptation during acute kidney injury). Drug‐induced hyperkalemia events are frequently combined with precipitating factors in hospitalized older patients and their prevention should focus on these combinations.